2006
DOI: 10.1159/000090990
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Lung Cancer

Abstract: The overall 5-year survival of lung cancer is only 10% in Europe and 15% in the United States, and progress in curative treatments during the last 20 years has been modest. Late diagnosis of extensive disease is the main reason of failure. Early detection with low-dose spiral computed tomography (CT) is one of the most promising development of clinical research, and continuous improvements in technology can make this instrument more effective than mammography in breast cancer detection. In order to prove the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 145 publications
2
31
0
Order By: Relevance
“…In the Mayo CT trial, the cumulative frequency of subjects with suspicious lesions was 74% at 5 years, but only 6% of them proved to have cancer, with a 70% rate of false-positive findings among all participants in the study (Swensen et al, 2005), whereas in the Milan study, using single-slice CT and a cutoff diameter above 5 mm, the frequency of subjects with suspicious lesions was only 19% at 5 years, 20% of whom proved to have cancer, with only 15% false-positive CTs overall (Pastorino, 2006). Nonetheless, the cumulative lung cancer detection rate was 4% in both trials (average 0.8% per year), with other major end points such as resectability and proportion of stage I disease being very similar.…”
Section: Issues Specific To Screening With Spiral Ct Prevalence Of Famentioning
confidence: 83%
“…In the Mayo CT trial, the cumulative frequency of subjects with suspicious lesions was 74% at 5 years, but only 6% of them proved to have cancer, with a 70% rate of false-positive findings among all participants in the study (Swensen et al, 2005), whereas in the Milan study, using single-slice CT and a cutoff diameter above 5 mm, the frequency of subjects with suspicious lesions was only 19% at 5 years, 20% of whom proved to have cancer, with only 15% false-positive CTs overall (Pastorino, 2006). Nonetheless, the cumulative lung cancer detection rate was 4% in both trials (average 0.8% per year), with other major end points such as resectability and proportion of stage I disease being very similar.…”
Section: Issues Specific To Screening With Spiral Ct Prevalence Of Famentioning
confidence: 83%
“…Pulmonary function tests and assessment of FEV1 should be considered when constructing strategies for lung cancer screening, in order to improve selection criteria. In fact, the frequency of benign lesions with last generation multi-slice CT is o50 times higher than lung cancer detection rate (,1% per yr) [38][39][40]. As a consequence, very large numbers of subjects have to be recruited in early lung cancer detection programmes, with a high chance of false-positive results, elevated costs and potential morbidity for the screened population.…”
Section: Discussionmentioning
confidence: 99%
“…These include the Danish Lung Cancer Screening Trial (DLCST), Multi-centric Italian Lung Detection Trial (MILD), 38,39 Italian Lung cancer Computed Tomography screening trial (ITALUNG), 40,41 Detection and screening of early lung cancer by Novel imaging Technology and molecular assays trials in Italy 42 and the French randomised pilot study, Depiscan. 43 ITALUNG, 41 MILD 38 and DLCST 44 have all reported on their mortality data, which showed no difference in the CT-screened arm; however, none of the studies was powered to provide such a result. 39,41,44 A summary of the European randomised lung cancer screening trials is shown in Table 1.…”
Section: European Lung Cancer Screening Trialsmentioning
confidence: 99%